POSSIBILITIES OF USING MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE PROVISION OF EDUCATIONAL SERVICES - Tokhirov Javlon Rakhimovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to the possibilities of using modern information and communication technologies in the provision of educational services, the possibilities of using 7 platforms in the provision of online educational services are analyzed. Summing up the results of the analysis, we came to general conclusions about the use of platforms.